Toxocara species environmental contamination of public spaces in New York City. - Donna L Tyungu; David McCormick; Carla Lee Lau; Michael Chang; James R Murphy; Peter J Hotez; Rojelio Mejia; Henry Pollack (Public Library of Science (PLoS), 2020)
Human toxocariasis has been identified as an under-diagnosed parasitic zoonosis and health disparity of significant public health importance in the United States due to its high seropositivity among socioeconomically disadvantaged groups, and possible links to cognitive and developmental delays. Through microscopy and quantitative PCR, we detected that Toxocara eggs are widespread in New York City public spaces, with evidence of significant levels of contamination in all five boroughs. The Bronx had the highest contamination rate (66.7%), while Manhattan had the lowest contamination rate (29.6%). Moreover, infective eggs were only found in the Bronx playgrounds, with over 70% of eggs recovered in embryonic form and the highest egg burden (p = 0.0365). All other boroughs had eggs in the pre-infectious, unembronyated form. Toxocara cati, the cat roundworm, was the predominant species. These results suggest that feral or untreated cats in New York City represent a significant source of environmental contamination. These findings indicate that human toxocariasis has emerged as an important health disparity in New York City, with ongoing risk of acquiring Toxocara infection in public spaces, especially in poorer neighborhoods. There is a need for reducing environmental Toxocara contamination. Additional rigorous public health interventions should explore further approaches to interrupt transmission to humans.